2008
DOI: 10.1097/scs.0b013e31815c94f5
|View full text |Cite
|
Sign up to set email alerts
|

Structural Fat Grafting in Complex Reconstructive Surgery

Abstract: The use of adipous tissue transfer for the correction of maxillo-facial defects was reported for the first time at the end of the 19 century and has been the subject of numerous studies. Grafted fat tissue has been used for years as an excellent filler during facial enhancement and recontouring. Several techniques have been proposed for harvesting and grafting the fat. However, due to the damage caused by excessive adipose tissue during these maneuvers, the results were not satisfying. The situation required a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 16 publications
0
83
0
1
Order By: Relevance
“…[1][2][3][4][6][7][8][9][10][11][12][13][14][15][16] Nine of the 15 studies were classified as level IV (case series), two as level III (a retrospective cohort and a comparative clinical study), one as level II (prospective cohort study), and three were not classified (for dealing with animal studies or review articles). No level I studies were found, that is, those with the strongest evidence (controlled and randomized clinical trials).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][6][7][8][9][10][11][12][13][14][15][16] Nine of the 15 studies were classified as level IV (case series), two as level III (a retrospective cohort and a comparative clinical study), one as level II (prospective cohort study), and three were not classified (for dealing with animal studies or review articles). No level I studies were found, that is, those with the strongest evidence (controlled and randomized clinical trials).…”
Section: Resultsmentioning
confidence: 99%
“…2,3,9 -12 Some authors 3,12 add that it is potentially permanent too, but others 21,22 claim results are inconsistent and uncertain. From Coleman's technique, different approaches for fat harvesting, processing, and injection were suggested for improving the cosmetic outcome and graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] For its volumetric qualities and regenerative capacity, fat harvesting was suggested in many facial asymmetries: after trauma, post-tumor resection, congenital complex, and hemifacial asymmetry (Franceschetti and Romberg syndromes). 4,[13][14][15][16][29][30][31][32][33][34] Our best results, following the traditional Coleman technique, were performed in the treatment of genetically determined syndromes, such as the Franceschetti and Romberg syndromes. Autologous fat transportation appears, particularly indicated in complex reconstructive surgery, as a powerful tool to improve facial aesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations